2012
DOI: 10.1074/jbc.m112.361139
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible Factor-1α (HIF1α) Switches on Transient Receptor Potential Ankyrin Repeat 1 (TRPA1) Gene Expression via a Hypoxia Response Element-like Motif to Modulate Cytokine Release

Abstract: Background: TRPA1 forms Ca 2+ - and Zn 2+ -permeable ion channels that sense noxious substances. Results: TNF-α and IL1-α induce TRPA1 gene expression via nuclear factor-κB signaling and downstream activation of HIF1α. Conclusion: HIF1α links inflammatory mediators to ion channel expression. Significance: HIF1α acts by binding to a specific hypoxia response ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
105
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 99 publications
(114 citation statements)
references
References 46 publications
8
105
1
Order By: Relevance
“…1, C and D). The evoked currents had a similar I-V relationship to that induced by MO, a typical TRPA1 agonist (11). After withdrawal of DPI, these evoked currents were abolished.…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations
“…1, C and D). The evoked currents had a similar I-V relationship to that induced by MO, a typical TRPA1 agonist (11). After withdrawal of DPI, these evoked currents were abolished.…”
Section: Resultsmentioning
confidence: 60%
“…TRPA1 expression in HEK cells transfected with TRPA1 plasmid (HEK-TRPA1 cells) was confirmed using the following three assays, as previously described (11,12): TRPA1 mRNA transcript expression, TRPA1 protein expression (see Fig. 5A) and TRPA1 channel function (see Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…To further confirm that the CCL20 gene is regulated directly by hypoxia through a HRE [(A/G)CGTG); refs. [30][31][32], high-scoring HRE-like sequences in the CCL20 gene promoter were identified by bioinformatics analysis. Moreover, a ChIP assay using an anti-HIF-1a showed that the putative HRE in the promoter of the CCL20 gene (AGAAGGCGTGTTGCCACA) was captured (Fig.…”
Section: Hif-1a Induces the Expression Of The Cytokine Ccl20 By Mesenmentioning
confidence: 99%